2022
DOI: 10.1007/s15010-022-01949-x
|View full text |Cite
|
Sign up to set email alerts
|

Cidofovir for treating complicated monkeypox in a man with acquired immune deficiency syndrome

Abstract: In July 23, the World Health Organization (WHO) declared monkeypox (MPX) a global health emergency of international concern given its rapid spread. So far, most current MPX outbreaks have involved young men who have sex with men (MSM), although with overall mild, self-limiting clinical manifestations. We aim to describe the case of an HIV positive young MSM whose status of immune compromission probably contributed to a more severe clinical course of MPX disease, thus requiring hospitalization and antiviral tre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 15 publications
0
12
0
2
Order By: Relevance
“…The antiviral tecovirimat prevents the release, spread, and pathogenicity of enveloped viruses by inhibiting the activity of the protein p37 [ 47 ]. MPXV DNA synthesis is slowed by cidofovir [ 48 ]. Brincidofovir is effective against viruses with double-stranded DNA and works as an antiviral by entering infected cells [ 49 ].…”
Section: Discussionmentioning
confidence: 99%
“…The antiviral tecovirimat prevents the release, spread, and pathogenicity of enveloped viruses by inhibiting the activity of the protein p37 [ 47 ]. MPXV DNA synthesis is slowed by cidofovir [ 48 ]. Brincidofovir is effective against viruses with double-stranded DNA and works as an antiviral by entering infected cells [ 49 ].…”
Section: Discussionmentioning
confidence: 99%
“…Recently, the real‐life use of cidofovir for the treatment of severe cases of Mpox has shown success in a small series of cases, with no adverse events reported 95 . In frail subjects, such as AIDS patients requiring hospitalisation for a severe course of Mpox, Cidofovir may also be considered as a valuable component of treatment 96 . In addition, another antiviral, tecovirimat, could be used for the treatment of Mpox.…”
Section: Discussionmentioning
confidence: 99%
“…95 In frail subjects, such as AIDS patients requiring hospitalisation for a severe course of monkeypox, Cidofovir may also be considered as a valuable component of treatment. 96 In addition, another antiviral, tecovirimat, could be used for the treatment of monkeypox. In fact, a preliminary study identified that oral tecovirimat was well tolerated by 25 males (age range: 26-76) with monkeypox infection, with minimal adverse effects.…”
Section: Practice and Research Implicationsmentioning
confidence: 99%
“…There are currently no antiviral drugs explicitly approved for the treatment of MPXV infection. The antiviral cidofovir has rarely been used as an off-label treatment for MPXV in humans and, although reported to be efficacious, further clinical investigation is necessary [20][21][22]. Tecovirimat, another antiviral that was designed and previously approved for the treatment of smallpox infection, was recently approved by the European Medical Association for the treatment of MPXV infection and is recommended in the treatment of severely ill individuals who are immunocompromised [23,24].…”
Section: Vaccine and Treatmentmentioning
confidence: 99%
“…While the similarities in the different species can complicate the diagnosis, many orthopoxviruses are cross-reactive and cross-protective, which can be beneficial. Sudden-onset fever with mucocutaneous lesions 1-3 days later Headache, lymphadenopathy, myalgia, back pain, asthenia [12,13] Human: corneal opacities, opaque pupil, erythematous sclera [14,15] GPR: corneal opacities and ocular discharge [16] Prairie dog: periocular lesions [17] Vaccines: modified vaccinia vaccine, ACAM200, JYNNEOS TM [13,18,19] Treatment: cidofovir (off-label) [20][21][22], tecovirimat to treat severely ill immunocompromised individuals [23,24] Variola virus (VARV) or Smallpox Human Incubation period: 7-19 days Prodromal phase with fever, malaise, headaches for 2-4 days Maculopapular rash progressing to pustules and scabs that form scars [25,26] Corneal ulceration with associated perforation, hypopyon, and iris prolapse [27][28][29] Posterior segment findings: retinitis, chorioretinitis, optic neuritis [29] Ocular vaccinia: conjunctival and corneal involvement or posterior segment complications [30][31][32][33] Vaccine: made from live vaccinia [34] Treatment: cidofovir, brincidofovir, tecovirimat [35][36][37][38] Cowpox virus (CPXV) Human Cat Cattle Elephant Rodent Incubation period: 8-12 days [39] Fever and lymphadenopathy Painful macular lesion that becomes hard black eschar with edema and erythema [40,41] Eyelid Incubation period: 9-13 days [53] Fever, lymphadenopathy, skin lesions [54] Eyelid lesions and retinal lesions leading to blindness [55] Vaccine: attenuated and inactiva...…”
Section: Introduction (Orthopoxviruses)mentioning
confidence: 99%